Guru Madrasah Ideal di Era Kontemporer - Noer Rohmah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
Globalization has direct parents to choose madrassa as an alternative education for their children. Fearing the impact of globalization, called “contemporary moral’s problems” causes the parents need to provide their children with religion, by sending them in the madrassa. It is hoped that not only being a clever and skillful figure, their children will also have good morals in accordance with Islamic values. To realize this, it is needed ideal teacher who effectively gives a significant impact on the development of students' knowledge and morale. This article presents the ideal profile of madrassa teacher needed in todays contemporary era. Various problems with the teacher’s quality of madrasah are also presented, added with their central role for students. The study hoped will provide insights for madrassa teachers to understand their important role in realizing the goal of Islamic education. Thus, they pleased to become the ideal figure of the madrassa teachers.